2013
DOI: 10.1002/er.3006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by alcoholysis of sodium borohydride

Abstract: SUMMARY Alcoholysis of sodium borohydride offers advantages due to reduction in number of steps for recycling of sodium borohydride, elimination of freezing problems that are associated with the use of water, fast generation of hydrogen, etc. Methanol was used to liberate hydrogen from sodium borohydride. The influence of the amount of solvent, substrate concentration, temperature and catalyst on the kinetics of alcoholysis reaction in non‐stabilized sodium borohydride has been examined in the present study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…Interestingly, there is almost no report of low‐temperature hydrolysis of NaBH 4 that may have significant impact on real‐time applications in automobiles and portable appliances . Therefore, alcoholysis studies of NaBH 4 have recently been reported as they offer additional advantages such as fast production of H 2 , easily regeneration of reaction products to NaBH 4 , and the elimination of freezing problems that are associated by the use of water. Various alcohols such as ethanol , 1,2 ethane diol , glycerol , and methanol have been used for the H 2 production from NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there is almost no report of low‐temperature hydrolysis of NaBH 4 that may have significant impact on real‐time applications in automobiles and portable appliances . Therefore, alcoholysis studies of NaBH 4 have recently been reported as they offer additional advantages such as fast production of H 2 , easily regeneration of reaction products to NaBH 4 , and the elimination of freezing problems that are associated by the use of water. Various alcohols such as ethanol , 1,2 ethane diol , glycerol , and methanol have been used for the H 2 production from NaBH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, alcoholysis studies of NaBH 4 have recently been reported as they offer additional advantages such as fast production of H 2 , easily regeneration of reaction products to NaBH 4 , and the elimination of freezing problems that are associated by the use of water. Various alcohols such as ethanol , 1,2 ethane diol , glycerol , and methanol have been used for the H 2 production from NaBH 4 . Nevertheless, a process for H 2 production that can provide the potential to be used in both portable and automotive applications even in colder climates by using a primary alcohol such as methanol as solvent instead of water may offer an alternative because of its lower freezing point, −97.6 °C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its properties such as low ignition temperature and rapid burning capacity are unmatched by other fuels. Hydrogen can be derived from a variety of sources (natural gas, coal, oil, water and biomass) through a number of processes (electrochemical, photochemical, photocatalytic, photoelectrochemical, thermochemical and biochemical) [12][13][14]. Nonetheless, there are some limitations in the storage and handling of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the methanol solvent present in the alcohols is of interest in the use of SB instead of water in the HP. In these studies, it was stated that the preference of methanol solvent instead of water was more effective in the HP . The acidity value of the methanol in the alcohol is higher than the acidity value of the water, which may be the possible cause of this result.…”
Section: Introductionmentioning
confidence: 99%